Protection of environmental assets in urban Africa: Regional and Sub-Regional Human Rights and Practical Environmental Protection Mechanisms. Issue 2 (4th May 2018) - Addaney, Michael; Boshoff, Elsabé; Nyarko, Michael Gyan
ABSTRACT: The rapid urbanisation in Africa is resulting in the vigorous degradation of the continent's environmental resources, especially in urban areas. There is also a growing fear that African governments may become locked into a 'grow dirty now, clean up later' development path that may be irreparable, expensive and wasteful. This may also result in a reduction of the welfare of all city dwellers, especially vulnerable groups. This trajectory has negative impacts on environmental rights and particularly the human rights of vulnerable individuals and communities to health, food, water and housing. Adopting a doctrinal method and a human rights-based approach, this article explores the intersection between human rights and environmental protection in the context of rapid urbanisation on the African continent. The main aim of the article is to examine whether, and to what extent, a regional human rights approach to environmental protection safeguards environmental assets in the context of urbanisation at the national level in Africa. The article discusses the nexus between human rights and environment protection in the African context and addresses key issue of human rights and environmental conservation in the context of urbanisation.